EXISTENCE ANALYSIS PT. ESAPUTLII MAIN INITIATIVE IN IMPROVING THE COMMUNITY ECONOMY IN MALLUSETASI DISTRICT, BARRU REGENCY - Jam’an, Jam’an; Asdar, Asdar; Naidah, Naidah; Naffalah, Egri Zakila (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
This study aims to determine how the existence of PT. Esaputlii Prakarsa Utama in improving the economy of the community in Mallusetasi District, Barru Regency. This type of research used in this research is qualitative research with descriptive methods. The research location was carried out in the area around the PT. Esaputlii Prakarsa Utama in Mallusetasi District, Barru Regency. The data source used is primary, namely data obtained directly from the field through informants. While the data collection techniques used in-depth interviews, observation, and document study. For data analysis techniques by performing data reduction, data presentation, and drawing conclusions. The results showed that with the establishment of PT. Esaputlii Prakarsa Utama in Mallusetasi District can provide benefits and changes to the community's economy. Because it will open up and increase the number of employment opportunities, such as the absorption of labor, and can increase business opportunities for the surrounding community so that the income of the majority of the community increases and is able to meet their needs.